Mechanisms of resistance to the mechanical damage of Tagosodes orizicolus (Muir) (Sogatodes orizicola) in rice - TRIANA-E., MÓNICA; PINEDA, ALICIA; PARDEY, CATHERINE; PANTOJA, ALBERTO; DUQUE, MYRIAM CRISTINA (Revista Colombiana de Entomología, 1994)
Tagosodes orizicolus (Muir) oviposition and nymphal survival were studied on 11 rice cultivars. Six cultivars recorded a low damage rate by sogata. The six materials were: Tetep, Mudgo, IRAT 124, IRAT 120, Amistad 82, and Makalioka. The cultivars IRAT 124 and Makalioka showed antibiosis while Tetep displayed a preference type of resistance. More eggs were collected from the foliage as compared to the stem. Leaf number 2 was more preferred for oviposition than leafs 1, 3, and 4.